PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN HARGA TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA SIGIT KOMPUTER SITUBONDO - Nona Ina; Mohammad Yahya Arief; Minullah Minullah (Fakultas Ekonomi dan Bisnis, 2025)
In this rapidly evolving era, everyone competes to open businesses, from culinary to electronics businesses. Sigit Komputer is one such business in Situbondo that specializes in electronics. Sigit Komputer handles various computer and laptop complaints, including hardware and software repairs. This study aims to analyze the effect of service quality, promotion, and price on consumer loyalty, with consumer satisfaction as an intervening variable at Sigit Komputer Situbondo. The sample size was 90 Sigit Komputer respondents in Situbondo. The sampling technique was simple random sampling. This study’s data analysis and hypothesis testing used the Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the Direct Hypothesis Test using the Smart PLS 3.0 application indicate that service quality has a significant positive effect on customer satisfaction, promotion has a positive but insignificant effect on customer satisfaction, price has a significant positive effect on customer satisfaction, service quality has a significant negative effect on customer loyalty, promotion has a positive but insignificant effect on customer loyalty, price has a significant positive effect on customer loyalty, customer satisfaction has a positive but insignificant effect on customer loyalty, service quality has a positive but insignificant effect on customer loyalty through customer satisfaction, promotion has a positive but insignificant effect on customer loyalty through customer satisfaction, and price has a significant positive effect on customer loyalty through customer satisfaction.